IN-VITRO BIOEQUIVALENCE STUDY FOR MARKETED INNOVATOR AND THREE BRANDS LOCAL MANUFACTURING CIPROFLOXACIN HYDROCHLORIDE TABLETS IN YEMEN - Alzomor, Abdulkarim K. Y.; Al-Madhagi, Wafa M.; Aljbry, Moath; Almontser, Seyaf; Al-Absi, Saeed; Khalid, Moneef (Universal Journal of Pharmaceutical Research, 2022)
Background and objective: This study is focused to evaluate the in vitro bioequivalence of three brands of ciprofloxacin 500mg tablets from local producer and marketing in Yemen, with innovator brand using in vitro dissolution study under biowaiver conditions by UV spectrophotometer. Method: The Dissolution profile has been evaluated by testing in dissolution media were USP buffer solution at pH 1.2 (hydrochloric acid solution), pH 4.5 (acetate buffer solution) and pH 6.8 (phosphate buffer solution). Also, further general quality assessment tests of these tablets like weight variation, disintegration time hardness, friability and assay test were accomplished according to proven methods. Results: All brands conformed to the official specification for uniformity of weight, friability and disintegration time. Content uniformity of chosen tablets shown that all samples contained over 99% (w/w) of labeled chemical content. The profile dissolution finding of all the tablets formulation and the innovator brand were further analyzed with difference factor (f1) and similarity factor (f2). Conclusion: These results indicated that the generic Cipro® (C) tablets included in this study was bioequivalent with the chosen innovator brand at 0.2N hydrochloric acid solution, pH 1.2 and the other generic brands bioequivalent with the chosen innovator brand at this medium. Also, the results showed that the three generic ciprofloxacin tablets involved in this study were bioequivalent with the selected innovator brand at pH 4.5 and pH 6.8. Peer Review History: Received: 7 August 2022; Revised: 16 September; Accepted: 23 October; Available online: 15 November 2022 Academic Editor: Dr. Amany Mohamed Alboghdadly , Princess Nourah bint abdulrahman university, Riyadh, amalbgadley@pnu.edu.sa Reviewers: Dr. Evren Alğin Yapar, Turkish Medicines and Medical Devices Agency, Turkiye, evren.yapar@yahoo.com Dr. George Zhu, Tehran University of Medical Sciences, Tehran, Iran, sansan4240732@163.com